2020
DOI: 10.1177/0308022620920535
|View full text |Cite
|
Sign up to set email alerts
|

‘You actually see what occupational therapists do in real life’: Outcomes and critical features of first-year practice education placements

Abstract: Introduction First-year practice education placements have numerous benefits for occupational therapy students but are resource intensive. In considering alternatives, it is critical to consider students’ voices to ensure that planned experiences enable students to achieve the outcomes they value and need. This study examined undergraduate occupational therapy students’ views about important outcomes and characteristics of first-year placements. Methods Focus groups were conducted with 18 occupational therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…More tacit learning about the profession, such as understanding the role of the Occupational Therapist in a particular setting (Mulholland and Derdall, 2007;Britton and Rehmel, 2019;Honey and Penman, 2020) and learning in the domain of cultural competency (Dyck and Forwell, 1997;Nielsen et al, 2017;Sonn and Vermeulen, 2018) have also previously been reported. Learning about service users could also be argued as identified within existing learning outcomes, although participants identified more nuanced learning than can reasonably be captured in this way.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…More tacit learning about the profession, such as understanding the role of the Occupational Therapist in a particular setting (Mulholland and Derdall, 2007;Britton and Rehmel, 2019;Honey and Penman, 2020) and learning in the domain of cultural competency (Dyck and Forwell, 1997;Nielsen et al, 2017;Sonn and Vermeulen, 2018) have also previously been reported. Learning about service users could also be argued as identified within existing learning outcomes, although participants identified more nuanced learning than can reasonably be captured in this way.…”
Section: Discussionmentioning
confidence: 95%
“…More tacit learning about the profession, such as understanding the role of the occupational therapist in a particular setting (Britton and Rehmel, 2019; Honey and Penman, 2020; Mulholland and Derdall, 2007) and learning in the domain of cultural competency (Dyck and Forwell, 1997; Nielsen et al, 2017; Sonn and Vermeulen, 2018) have also previously been reported.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations